Pengembangan Video Pembelajaran Materi Ikatan Kimia Dengan Model ADDIE Sebagai Penunjang Pembelajaran Di Masa Pandemi COVID-19 - Meylin Kawete; Dokri Gumolung; Anderson Aloanis (Oxygenius Journal Of Chemistry Education, 2022)
The purpose of this study was to develop a Learning Video for Chemical Bonding Materials with the Addie Model as Learning Support during the Covid-19 Pandemic. This research is research and development (Research and Development). This research is a research that refers to the ADDIE model (Analysis, Design, Development or Production, Implementation or Delivery and Evaluations). By following the fifth stage of the ADDIE model, because this is a Video Development research, this research only reaches the fourth stage, namely the Implementation stage. Data collection techniques in this study used a Validation Questionnaire (validation of media experts and validation of material experts) and Student Response Questionnaires. The results of the first material expert validation are included in the "very feasible" criteria with a percentage of 80%. The results from the second validation questionnaire are included in the 'very feasible' criteria with a percentage of 100%, the results from the first media expert validation questionnaire with the 'very feasible' criteria with a percentage of 95.12%, the results from the second validation questionnaire are included in the 'very feasible' criteria with a percentage 86.66% and the results of the student response questionnaires are included in the "very feasible" criteria with a percentage of 90%. Learning videos are declared very suitable for use in the learning process.